Tinjauan Maṣlaḥah Ḥifẓ Al-Māl Terhadap Pelaksanaan Akad Kerjasama Bagi Hasil Di Desa Sumberdodol Kecamatan Panekan Kabupaten Magetan - Aima Mar’atus Solihah (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
This research purpose: 1) To find out the maslahah and mafsadah elements of implementing the production sharing agreement in Sumberdodol Village Panekan District Magetan Regency. 2) To determine the level of maslahah hifz al-mal on the production sharing agreement in Sumberdodol Village Panekan District Magetan Regency. The type of research conducted by the author is field research using qualitative methods, while the data collection techniques used are interviews and observation. From this research, it can be concluded that 1) The maslahah element in implementing the production sharing agreement in Sumberdodol village is that the garden owner has prospered the farm cultivator by providing a good job. Farmers can work to supplement their family’s needs. While the element of mafsadah is the distribution of results that is not under the agreement, and the cultivator does not yet know the deadline for the end of the collaboration. 2) The level of maslahah hifz al-mal in cooperation for profit-sharing in the village of Sumberdodol is included in the Hajiyah level. Its existence is needed to provide convenience and eliminate difficulties in human life. Because cultivators and gardeners both provide convenience and benefits.